Experiments on mixed convection in a vented differentially side-heated cavity filled with a coarse porous medium. (March 2020) - Ataei-Dadavi, Iman; Chakkingal, Manu; Kenjeres, Sasa; Kleijn, Chris R.; Tummers, Mark J.
Highlights: Nusselt number measurements in a wide range of Reynolds and Rayleigh numbers resulting in a Richardson number between 0.1 to 100. Particle image velocimetry (PIV) and Liquid crystal thermography (LCT) measurements using a refractive index matched porous medium. Higher Nusselt number for the cavity with porous medium as compared to the pure-fluid cavity at high Reynolds numbers. Three flow and heat transfer regimes depending on Richardson number. New correlation for Nusselt number as a function of Reynolds and Rayleigh numbers. Abstract: This paper reports on an experimental study of mixed convection flow and heat transfer in a vented, differentially side-heated cubical cavity filled with a porous medium consisting of relatively large solid low-conductivity spheres. Rayleigh numbers and Reynolds numbers are varied over the ranges 6 × 10 6  < Ra < 7 × 10 7 and 240 <  Re  < 4250, respectively, for a fixed Prandtl number of Pr = 6.75, thus covering more than three decades in Richardson numbers Ri = Ra/(Re 2 Pr). Heat transfer measurements were combined with measurements of the velocity field (using particle image velocimetry) and the temperature field (using liquid crystal thermography) to better understand the dependence of the Nusselt number, Nu, on the Richardson number. We observed three different flow and heat transfer regimes depending on the Richardson number. For Ri < 10, the flow structure and the Nusselt number scaling are similar to those for the pure forced convection, i.e., the Nusselt number scales as Nu ~ Re 0.61 independent of Rayleigh number. For Ri > 40, natural convection dominates the flow in the vicinity of the heating wall. The Nusselt number becomes less sensitive to the Reynolds number and is mainly determined by the Rayleigh number. In the intermediate regime for 10 < Ri < 40, the upward directed natural convection flow at the heating wall competes with the downward directed forced flow leading to a minimum effective Nusselt number. A Nusselt number correlation is derived that is valid in the range 0.1 < Ri < 100 covering all three regimes.